1985
DOI: 10.1080/00420988520080851
|View full text |Cite
|
Sign up to set email alerts
|

Transport, Land Use and Energy Interaction

Abstract: An analysis of data from London and Paris, using directly comparable methods of expressing all results in terms of distance from the centre, is undertaken of the following variables: population density, mean household income, car ownership, median daily travel time per traveller, and energy consumption. It is argued that the results demonstrate that population density and public transport provision are far less important influences on energy consumption than car ownership, and that it follows that economising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
0
2

Year Published

1988
1988
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 3 publications
6
28
0
2
Order By: Relevance
“…e coefficient of this factor therefore captures the portion of the effect of these characteristics that is related to energy use for transport (Smits 2003, 3). e results of the Hangzhou Metropolitan Area study are well in accordance with the conclusions from studies in Paris (Fouchier 1998;Mogridge 1985), London (Mogridge 1985), New York and Melbourne (Newman and Kenworthy 1989), San Francisco (Schipper et al 1994), Oslo (Naess et al 1995), Dutch urban regions (Schwanen et al 2001), English cities (Stead and Marshall 2001), Danish provincial cities (Harto -Nielsen 2001;Nielsen 2002;Naess and Jensen 2004), the Copenhagen Metropolitan Area (Naess 2005(Naess , 2006a, and Santiago de Chile (Zegras 2010). e results thus seem to be of a high generality, indicating that the dominant mechanisms by which residential location in uences urban travel will be present across city sizes and despite considerable contextual differences.…”
Section:         ()supporting
confidence: 73%
See 1 more Smart Citation
“…e coefficient of this factor therefore captures the portion of the effect of these characteristics that is related to energy use for transport (Smits 2003, 3). e results of the Hangzhou Metropolitan Area study are well in accordance with the conclusions from studies in Paris (Fouchier 1998;Mogridge 1985), London (Mogridge 1985), New York and Melbourne (Newman and Kenworthy 1989), San Francisco (Schipper et al 1994), Oslo (Naess et al 1995), Dutch urban regions (Schwanen et al 2001), English cities (Stead and Marshall 2001), Danish provincial cities (Harto -Nielsen 2001;Nielsen 2002;Naess and Jensen 2004), the Copenhagen Metropolitan Area (Naess 2005(Naess , 2006a, and Santiago de Chile (Zegras 2010). e results thus seem to be of a high generality, indicating that the dominant mechanisms by which residential location in uences urban travel will be present across city sizes and despite considerable contextual differences.…”
Section:         ()supporting
confidence: 73%
“…Fouchier 1998;Mogridge 1985;Kenworthy 1989, 1999;Naess 2006b;Naess and Jensen 2004;Naess et al 1995;Schwanen et al 2001;Stead and Marshall 2001;Zegras 2010). ese relationships between residential location and travel behavior make up an important part of the foundation for the policies of planning authorities in several European countries aiming to promote compact and concentrated urban development.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies-internationally as well as in the Nordic countries-have treated car ownership as an exogenous control variable and thus ignored the influence of residential location on car ownership, the two-way influence characterizing this relationship is increasingly being acknowledged in the international research (Giuliano & Narrayan 2003;Scheiner & Holz-Rau 2007, Vance & Hedel 2008Zegras 2010;Aditjandra et al 2010). Similar strong influences of residential location relative to the city center on traveling distances (in total or by car) as those found in the Nordic studies have also been identified in a number of other cities around the world, including Paris (Mogridge 1985;Fouchier 1998); London (Mogridge ibid. ); New York and Melbourne (Newman and Kenworthy 1989); San Francisco (Schipper et al 1994); Austin, Texas (Zhou & Kockelman 2008); Athens (Milakis, Vlastos and Barbopoulos); Hangzhou (Naess 2009b and, and Santiago de Chile (Zegras 2010).…”
Section: Discussionmentioning
confidence: 53%
“…8. This mix of clusters indicates the highly varied density histories of metropolitan edges, reflecting both checkerboard or leapfrog development, and the incorporation of pre-existing small urban centers (Morgridge, 1985). In rural areas, 1990 housing density and 1940-1990 density clusters (Figs.…”
Section: Housing Density Clustersmentioning
confidence: 99%